2005
DOI: 10.3748/wjg.v11.i12.1862
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distinctions between autoimmune hepatitis in Italy and North America

Abstract: HLA DR4 is not associated with AIH in Italy. The known HLA risk factors for AIH occur similarly in Italian patients with type 1 and type 2 AIH, and they are less frequent than in North American patients. B8-DR3-DQ2 is the predominant phenotype of type 1 AIH also in Italy, and HLA DR11 may be a regionally distinctive protective factor against type 1 AIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 33 publications
8
45
2
2
Order By: Relevance
“…No significant increase was observed in DRB1*03 in the present study despite a higher frequency reported in studies from North America, West Asia and North Europe. In Italy, DR11 was significantly lower in type 1 AIH patients compared to controls, which is in contrast with our findings showing a significant increase in DRB1*11 (DR11) compared to controls (12% vs. 0%, p=0.001) (26).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…No significant increase was observed in DRB1*03 in the present study despite a higher frequency reported in studies from North America, West Asia and North Europe. In Italy, DR11 was significantly lower in type 1 AIH patients compared to controls, which is in contrast with our findings showing a significant increase in DRB1*11 (DR11) compared to controls (12% vs. 0%, p=0.001) (26).…”
Section: Discussioncontrasting
confidence: 56%
“…Another study from Germany reported C7, A2, B8, DR3, and DQ2 to be the most frequent HLA types in type 1 AIH (25). The authors compared their data with those obtained in Italy and North America (26). In the Italian study, B8, C7, DQ2 and DR3 showed a higher frequency in types 1 and 2 AIH compared to controls, and B8-DR3-DQ2 in type 1 compared to controls.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a study of 83 Chinese adult patients with AIH, there was no disparity in the frequency of CAIDs among the different age groups [17] . In another study from Italy, the occurrence of the CAIDs was also shown to be independent of the AIH subtype, gender, and the age of onset of the liver disease (children vs. adults; 22 vs. 16%, p = 0.495; 23.1 vs. 10.3%, p = 0.205; 17.8 vs. 22.2%, p = 0.803), respectively [10] .…”
Section: Effects Of Aih Types Age Gender and Genetic Backgroundmentioning
confidence: 99%
“…HLA DRB1,04 has been reported to be a significant risk factor in different studies (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The frequency of A24,9, A26, A32, DRB1,15 was high in our type-1 subjects, the frequency of A26, B51, DRB1,11 was high in our type 2 subjects and the frequency of A32 and DRB1,04 was found high in the undefined type.…”
Section: Discussionmentioning
confidence: 51%